Species Sensitivity to Toxic Substances: Evolution, Ecology and Applications - Spurgeon, David; Lahive, Elma; Robinson, Alex; Short, Stephen; Kille, Peter (Frontiers in Environmental Science, 2020)
Because it is only possible to test chemical for effects on a restricted range of species and exposure scenarios, ecotoxicologists are faced with a significant challenge of how to translate the measurement in model species into predictions of impacts for the wider range of species in ecosystems. Because of this challenge, within ecotoxicology there is no more fundamental aspect than understanding than the nature of the traits that determine sensitivity. To account for the uncertainties of species extrapolations in risk assessment, ‘safety factors’ or species sensitivity distributions are commonly used. While valuable as pragmatic tools, these approaches have no mechanistic grounding. Here we highlight how mechanistic information that is increasing available for a range of traits can be used to be understand and potentially predict species sensitivity to chemicals. We review current knowledge on how toxicokinetic, toxicodynamic, physiological and ecological traits contribute to difference in sensitivity. We go on to discuss how this information is being used to make predictions of sensitivity using correlative and trait-based approaches, including comparisons of target receptor orthologues. Finally, we discuss how the emerging knowledge and associated tools can be used to enhance theoretical and applied ecotoxicological research through improvements in mechanistic modelling, predictive ecotoxicology, SSD development, mixture toxicity assessment, chemical design, biotechnology application and mechanistically informed monitoring.